English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

f(x) = 1/2x + 3; f(4)---

f(x) = x/3 + 4; f(-9)---

f(x) = x + 4; f(2)---

f(x) = -3x + 2; f(-4)---

2006-10-30 14:17:09 · 4 answers · asked by precious_angel_amy34 2 in Science & Mathematics Mathematics

4 answers

Answer 1:
f(x) = (1/2x) + 3
f(-4) = 1/[(2)(-4)] + 3
= (1/-8) + 3
= (1-24)/-8
= -23/-8
= 23/8

Answer 2:
f(x) = x/3 + 4
f(-9) = -9/3 + 4
= -3 + 4
= 1

Answer 3:
f(x) = x + 4
f(2) = 2 + 4
= 6

Answer 4:
f(x) = -3x + 2
f(-4) = (-3)(-4) + 2
= 12 + 2
= 14

2006-10-31 02:07:15 · answer #1 · answered by Akilesh - Internet Undertaker 7 · 0 1

(1) Is the first question 1/2x (or) x/2 i.e (1/2)x ?

if it is (1/2)x , the others are correct

if it is 1/2x, then f(4) = 1/(2*4) + 3 = 1/8 + 3 = 25/8 = 3 1/8

(2) f(-9) = -1
(3) f(2) = 6
(4) f(-4) = 14

2006-10-30 23:10:13 · answer #2 · answered by Truth Seeker 3 · 0 0

f(4) means find the value of f(x) when x=4. Replace x with 4 in 1/2x + 3.

So f(4) = 1/2*4 + 3 = 5.

Now you try it for the rest...

2006-10-30 22:23:37 · answer #3 · answered by Anonymous · 0 1

5, 1, 6, 14

2006-10-30 22:19:23 · answer #4 · answered by Courtney C 2 · 0 2

fedest.com, questions and answers